A Comprehensive Examination of the Association Between the ACE2 Gene with the Susceptibility to COVID-19 and the Occurrence of Diabetes Mellitus (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:The rate of transmission, as well as the risk of death associated with COVID-19, is significantly higher than that of previous epidemics. Among the underlying health conditions frequently observed in affected populations, diabetes stands out as one of the most prevalent. Individuals with diabetes who contract Covid-19 face a heightened risk of disease progression compared to those with other conditions.Materials and Methods:A case-control study was implemented to assess biomarkers using classical lab work procedures and genetic markers using congenital PCR, then the association between ACE2 gene, COVID-19 and Diabetes Mellitus were implemented.Results:The analysis of the ACE2 (ID; DD) group revealed statistically significant differences between the groups. However, the II as well as I groups did not demonstrate any notable differences. The chi-square method employed, with a p-value set at < 0.05, indicating statistical significance. Among the manage organization, those with covid-19 , and humans with diabetes plus covid19, the ACE2 D genotype was the most common genotype, accounting for 72.6%, 85%, and 54% of the full population, respectively. After this, the DD, ID, and I genotypes have been applied to the samples.Conclusions:The ACE2 D genotype showed significant prevalence in COVID-19 and diabetes populations, while the II and I genotypes showed no notable differences, highlighting ACE2 D’s potential importance